12(3x+5)-6(2x-2)=4x-68

Simple and best practice solution for 12(3x+5)-6(2x-2)=4x-68 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(3x+5)-6(2x-2)=4x-68 equation:


Simplifying
12(3x + 5) + -6(2x + -2) = 4x + -68

Reorder the terms:
12(5 + 3x) + -6(2x + -2) = 4x + -68
(5 * 12 + 3x * 12) + -6(2x + -2) = 4x + -68
(60 + 36x) + -6(2x + -2) = 4x + -68

Reorder the terms:
60 + 36x + -6(-2 + 2x) = 4x + -68
60 + 36x + (-2 * -6 + 2x * -6) = 4x + -68
60 + 36x + (12 + -12x) = 4x + -68

Reorder the terms:
60 + 12 + 36x + -12x = 4x + -68

Combine like terms: 60 + 12 = 72
72 + 36x + -12x = 4x + -68

Combine like terms: 36x + -12x = 24x
72 + 24x = 4x + -68

Reorder the terms:
72 + 24x = -68 + 4x

Solving
72 + 24x = -68 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
72 + 24x + -4x = -68 + 4x + -4x

Combine like terms: 24x + -4x = 20x
72 + 20x = -68 + 4x + -4x

Combine like terms: 4x + -4x = 0
72 + 20x = -68 + 0
72 + 20x = -68

Add '-72' to each side of the equation.
72 + -72 + 20x = -68 + -72

Combine like terms: 72 + -72 = 0
0 + 20x = -68 + -72
20x = -68 + -72

Combine like terms: -68 + -72 = -140
20x = -140

Divide each side by '20'.
x = -7

Simplifying
x = -7

See similar equations:

| 2x+7=17-10x | | 16-8t=5-9t | | 0.75x+3.22=6.97 | | 1x+4=7x-3 | | 2(x+4)-3=4x-2(-5+x) | | 112-4x=4x-24 | | y+5(y-1)=7 | | (5x-2)(2x)=115 | | -43-2x=17-8x | | 7p+1=5p+25 | | 10=5+2x | | 24x^2+36=4x*h | | 2(c-1)=4(3-c) | | 4x^2+36x=4x*h | | 6x+29x-7=7(5x+4) | | 3y+9=2y-6 | | 6x^2-7x+3=0 | | 3r+8=3 | | 3(2-x)=x+2 | | 4x+36x=4x*h | | 5q-5=17 | | 2(3n-1)=(4n+8)+7 | | 2.00-.33=.22x | | 2t+6=21-t | | 5(5x+2)-9=25x+1 | | 8c=90-c | | 11-5y=4y+20 | | 65-5x=4x+23 | | 47x+1673x-15=43(40x+60) | | 11+5y=4y+20 | | 4(t+2)=18-t | | x^2+3x-2x=5x+1 |

Equations solver categories